KEANEKARAGAMAN KOMUNITAS KRUSTASEA DI KEPULAUAN MATASIRI KALIMANTAN SELATAN - Pratiwi, Rianta; Wijaya, Nirmalasari Idha (BERITA BIOLOGI, 2013)
Studies on the community diversity of crustaceans have been conducted in the waters of Matasiri Islands, South Kalimantan, from 19th November to 1st December 2010. This research was conducted to determine the density, diversity and the presence of crustacean fauna in the waters of South Kalimantan, especially in the Matasiri Islands. Samples were collected using trawl gear operated by KR (Research Ship) BarunaJaya VIII in four Stations and three Stations of free collecting along the islands. Free sampling was conducted along the beach and the reef edge by breaking live and dead rocks, and digging sand and mud in the mangrove or using hand net around the beach of Matasiri Islands. Collection is also done using the gillnet gear which is installed in shallow water during high tides about 4 hours.The samples were collected during low tide. The results obtained were 1882 individuals covering 86 species and 19 families. The diversity index ranges between 0.97 (the lowest at Station 3 of free collecting) and 3.74 (the highest in Station 3 of trawl). While the similarity index ranged from 0.36 (the lowest in Station 1 of trawl) to 0.97 (the highest in Station 3 of free collecting). Penaeidae prawn has the highest density in each observed station. Portunidae crab has the second highest density. South Kalimantan waters especially Matasiri Islands is still in good condition for crustacean life.